Scientific diving in Brazil: history, present and perspectives - Leite, Tatiana S. (2023)
Scientific diving (SD) is defined as any diving activity that applies scientific procedures to produce subsidies for studies and technical works in underwater environments. The first report of an underwater scientific study in Brazil dates to the 19th century, in the Abrolhos reefs. Currently, in Brazil, scientific diving has been performed in various areas, from shallow coastal regions to remote and sometimes hard-to-reach places, such as oceanic islands, flooded caves, and icy areas like Antarctica. However, the regulation of SD in Brazil still lacks more concrete actions towards an effective and efficient self-regulation that offers physical safety to practitioners and institutional safeguards for organizations that use it in their research projects. Thus, this article aims to contribute to a better understanding of this critical issue in Brazil and to serve as a reference and incentive for the training of professionals and the development of these activities in the country. It includes: 1) a historical review of SD; 2) a diagnosis of the training and application of SD in Brazil; 3) the evolution of marine sciences in Brazil from the perspective of SD; 4) a review of the use of environmental assessment and underwater conservation techniques in oceans and internal waters; 5) an analysis of the evolution of scientific diver training in Brazil, including a diagnosis on training; 6) the history and updates of the rules, regulations, and safety of SD. Given all the potential of diving combined with specific techniques for research, monitoring, and marine and limnic science in Brazil, we aim to understand the evolution of scientific diving teaching and to outline perspectives in the country, as it is crucial for the training of qualified scientists capable of performing these underwater tasks. Finally, we present future plans for the development of this activity in Brazil from the point of view of research and the labor market.